A formação inicial de professores de inglês como espaço para a (re)construção de identidades - Barbosa, Selma Maria Abdalla Dias [UNESP] (2014)
This ethnographic and longitudinal study is aimed at investigating, analyzing and understanding the complex process of professional, social and cultural identity (re)construction in pre-service teachers in a Teacher Education Course at a Federal University in the extreme north of Brazil. The pre-service teacher’s narratives were investigated through a qualitative approach. The narratives were collected from these students-teachers during the four semesters of their supervised internship class in their undergraduate course, as well as the interactions they posted in the Community of Practice-CdP (WENGER, 1998; CLARKE, 2008) and discussed in thematic sessions accomplished during the process of investigation. The narrative genres that called reflexive narratives are live histories and experiences the teacher-students experimented with and practiced while teaching English classes at public schools. These narratives are dialogued with the researcher-reader at specific moments. Then, we simultaneously intended to understand how this professional identity (re)construction happens and we also will analyze the cognitive (BORG, 2006; ZEICHNER, 2005; ZEMBYLAS, 2005) as well as the emotions and affective aspects (VIEIRA ABRAHÃO, 1992; 1996, 2004, 2006; BARCELOS, 2007, 2010; ARAGÃO, 2005; COELHO, 2011) which one experiences while negotiating identity as the foreign language teacher education process in a sociocultural perspective. The results indicate an interconnectedness of social, cognitive and emotional factors in the identity (re)construction in both face to face and virtual spaces of interaction. Furthermore, the narratives elicit the synchronic way of the complex process of identity construction as well as its flow and its transience. We also observed a major incidence of co-construction of professional identities in the Community of Practice’s (Moodle) interactions, showing itself mainly as a sharing of emotions, realizations, ...